Induced radiation studies and personnel dose assessment in a carbon ion therapy facility. (October 2022) - Luo, Changli; Li, Wuyuan; Yang, Bo; Su, Youwu; Li, Yang; Li, Zongqiang; Mao, Wang; Liu, Xuebo; Yan, Weiwei; Ma, Fuhong
Abstract: Carbon ions have become the most widely used particles in heavy-ion tumor therapy due to favorable physical and biological characteristics. The beam delivery system (BDS) and tumor tissues are directly bombarded with accelerated carbon ions, resulting in activation products in the components and the patient's body. The results of an experimental study and a Monte-Carlo simulation for the radioactivity induced in a treatment room under a uniform scanning mode were presented in this study. They indicated that the multi-leaf collimator (MLC) and the patient's body were the main sources of induced radioactivity. The half-lives of the main produced radionuclides ranged from a few minutes to tens of minutes for single irradiation and from dozens of days to hundreds of days for long-term irradiation. The personal dose of medical staff working in the treatment room and the additional dose of the patient from the induced radioactivity were estimated. Finally, some suggestions were made to reduce the unwanted radiation exposure of the medical staff, patients, and carers. Highlights: The Monte Carlo method and experimental method were used to study induced radioactivity of the treatment room. Induced radioactivity from single treatment and long-term irradiation were analyzed. The exposure doses of the concerned people (medical staff, carers, and patients) were assessed. Suggestions on how to reduce the exposure dose for the concerned population were given.